The art of “diplomacy” and its significance in the internal public life of the period of King Stanisław’s reign – some remarks about the clientelism and careers which were not accidental - Rolnik, Dariusz (Władza i polityka w czasach nowożytnych. Dyplomacja i sprawy wewnętrzne, 2020)
No doubt the art of “diplomacy” as a skill or talent was beneficial to those who pursued a career path in the period of King Stanisław’s reign. This property or capability made it easier for those who enjoyed it to make a career and it also made it easier for them to keep afloat in the public life. Such skills enabled a given person to stand out. However, the examples which are presented demonstrate the possibilities of the advancement of poor noblemen. In the period of King Stanisław’s reign advancement was determined by aptitude and talent. Even though connections and background were important factors, their significance diminished gradually but discernibly. However, this change did not entirely entail a change of the thinking about the state. The new criteria of the making of elites were not always associated with ideological questions. In many cases a senator who was created, now not owing to his connections or background but owing to his talent, aptitude and the eponymous “diplomatic talent”, thought in particularistic terms. Unfortunately, he did not always take into account the interests of the entire Rzeczpospolita. However, let us admit that he strove to combine his interests with the demands of the land in which he operated.